2014
DOI: 10.11646/zootaxa.3760.2.6
|View full text |Cite
|
Sign up to set email alerts
|

Three new species of Coecobrya (Collembola: Entomobryidae) <br />from southern and northwest China

Abstract: Three new species of Coecobrya are described from southern and northwest China. C. draconis sp. nov. from Guangxi cave shows some troglomorphic features, such as the inner ungual teeth inserted basally. C. xui sp. nov. is similar to C. huangi and differs from the latter by head and tergal chaetotaxy. C. qin sp. nov. is the second member of the genus with 3+3 eyes, but cannot be assigned to either the tenebricosa-or boneti-groups because it has eyes and a large outer tooth on unguiculus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
(4 reference statements)
0
6
0
Order By: Relevance
“…(3) Externally on coxae I, II and III [initially mentioned by Hüther (1962) as "chitinringe", and by Gisin (1963)]. (4) On manubrium between its basis and the genital plate, probably those observed in Coecobrya by Zhang & Dong (2014) and Zhang et al (2018), as a group of 2-3 in L. doveri.…”
Section: Pseudoporesmentioning
confidence: 99%
“…(3) Externally on coxae I, II and III [initially mentioned by Hüther (1962) as "chitinringe", and by Gisin (1963)]. (4) On manubrium between its basis and the genital plate, probably those observed in Coecobrya by Zhang & Dong (2014) and Zhang et al (2018), as a group of 2-3 in L. doveri.…”
Section: Pseudoporesmentioning
confidence: 99%
“…), Coecobrya (Zhang et al . , ; Zhang & Dong ), Lepidocyrtus (Deharveng ; Zhang et al . ), Homidia (Shi et al .…”
Section: Introductionmentioning
confidence: 99%
“…Patterns of S-chaetae in Entomobryidae were firstly illustrated by Szeptycki (1972Szeptycki ( , 1979 across Entomobryidae, but in broader focus of all chaetotaxy analysis. They were studied or incidentally mentioned later in a few species of Entomobrya (Jordana & Baquero 2005;Baquero & Jordana 2008), Orchesellides (Jordana & Baquero 2006), Seira (Soto-Adames 2008), Sinella (Zhang & Deharveng 2009, 2011Zhang 2013;Zhang et al 2014c), Coecobrya (Zhang et al 2009a(Zhang et al , 2011aZhang & Dong 2014), Lepidocyrtus (Deharveng 1979;Zhang et al 2009b), Homidia (Shi et al 2009a(Shi et al ,b, 2010 and Szeptyckiella (Zhang et al 2014b), while more sporadic records of incomplete S-chaetotaxy are found in many publications. Zhang et al (2011b) reported the patterns of tergal S-chaetotaxy and their variation in Sinella and Coecobrya.…”
Section: Introductionmentioning
confidence: 99%
“…5). Also in Coecobrya xui the presence of 2 pseudopores has been described on dorsobasal position of manubrium on position 13 (Zhang & Dong 2014).…”
Section: Subgenera and Species Groups In European Lepidocyrtusmentioning
confidence: 98%